Magnesium Intake and Risk of Colorectal Cancer: A Meta-analysis of Prospective Cohort Studies - Song, MD, ScD, Yiqing; Shah, MD, Hetal; Ma, MD, MS, Jiantao; He, MD, ScD, Ka; Dai, MD, PhD, Qi (North American Journal of Medicine and Science, 2009)
Background: Evidence from in vitro and in vivo studies indicates that magnesium may be involved in carcinogenesis. However, results from observational studies on dietary magnesium intake and colorectal cancer risk are inconsistent. Methods and Results: A meta-analysis of cohort studies was conducted to examine the association between magnesium intake and colorectal cancer. Studies were included if they provided a relative risk (RR) and corresponding 95% confidence interval (CI) for colorectal cancer in relation to total or dietary magnesium intake. A database was developed based on 4eligible studies including 255,826 individuals who were initially free of cancer with an average 14 years of follow-up. Pooled RR and 95% CI for colorectal cancer were calculated by using random-effect models. Compared with those in the lowest category of magnesium intake, individuals in the highest category had lower colorectal cancer; the pooled multivariate RRs were 0.81 (95% CI, 0.69-0.95) for total colorectal cancer, 0.81 (95%CI, 0.68-0.97) for colon cancer, and 0.84 (95% CI, 0.63-1.12) for rectal cancer.